NEIGHBOURHOOD ACCESSIBILITY AND ACTIVE LIVING PATTERN OF CHILDREN: A PILOT STUDY IN NAGPUR, INDIA - Pedram, Vaishali; Chakradeo, Ujwala (International Journal of Research -GRANTHAALAYAH, 2024)
Purpose: This paper explores the association between neighbourhood accessibility and the active living patterns (ALP) of children in urban India. Focusing on outdoor out-of-school physical activities (OOPA), mode of travel to school (MTS), mode of travel to the neighbourhood (MTN), and habitual active independent home range (HAIHR), it seeks to understand the relationship between active living and neighbourhood outdoor physical environment (OPE) during middle childhood. Methodology: Defining the variable within the framework of the ‘Adapted Ecological Model for Active Living in Urban Indian Children’, this study employed a cross-sectional quantitative method to examine two neighborhoods in Nagpur, India. The subjective data was collected from 43 in-person surveys of 8–12-year-old children and objective data was computed using GIS. Results: Children’s ALP had significant positive associations with built density, traffic exposure, parents’ perception of personal safety, neighbourhood physical activity (PA) environment, license for independent mobility (IM) and gender. Children’s OOPA was significantly positively correlated with built density, neighbourhood PA environment, motivation for PA, license for IM and gender. Children preferred active MTS to school if schools were close by and they had licenses for IM whereas their active MTN depended on parent’s positive perceptions of personal safety in the neighbourhood and permission for IM. Longer HAIHR was related to lesser traffic, licenses for IM and parents’ positive perceptions of neighbourhood safety. Conclusion: This study has identified several key neighbourhood OPE (density, traffic, parental safety concerns, PA environment), individual (gender, motivation), and interpersonal (license IM) correlates shaping urban children’s active living in India.